In-Situ Wettability Analysis of Al Coating Influence on Hot-Dip Galvanizing Properties of Advanced High-Strength Steels - Srinivasulu Grandhi; Kwang-Hyeok Jin; Min-Su Kim; Dong-Joo Yoon; Seung-Hyo Lee; Min-Suk Oh (Archives of Metallurgy and Materials)
We investigated the influence of steel surface properties on the wettability of zinc (Zn). Our main objective is to address the selective oxidation of solute alloying elements and enhance the wetting behavior of Zn on advanced high strength steel (AHSS) by employing an aluminum (Al) interlayer through the physical vapor deposition technique. The deposition of an Al interlayer resulted in a decrease in contact angle and an increase in spread width as the molten Zn interacted with the Al interlay on the steel substrate. Importantly, the incorporation of an Al interlayer demonstrated a significant improvement in wettability by substantially increasing the work of adhesion compared to the uncoated AHSS substrate.